Reform of Peer-to-Peer Lending Consumer Protection Legislation and Dispute Resolution - Ariawan Ariawan; Gulyamov Said Saidaxrarovich; Naeem Allahrakha (Contrarius, 2025)
The rapid growth of peer-to-peer (P2P) lending financial technology services in Indonesia has contributed significantly to expanding financial inclusion and improving economic efficiency. However, this development has simultaneously generated complex legal challenges, including violations of personal data protection, unethical debt collection practices, and the widespread operation of illegal fintech platforms. This study aims to examine the adequacy of the existing legal framework in providing effective consumer protection within the P2P lending sector and to assess its alignment with the principles of justice, legal certainty, and consumer rights protection. The research employs a normative juridical method, utilizing statutory and conceptual approaches to analyze relevant regulations governing fintech services in Indonesia. The findings reveal that current regulatory instruments demonstrate the state’s commitment to safeguarding consumers and ensuring fair digital financial practices. Nevertheless, the effectiveness of these regulations remains limited due to insufficient regulatory supervision, low levels of digital financial literacy among consumers, and persistent enforcement gaps against illegal fintech operators. This study concludes that consumer protection in P2P lending requires a more substantive justice-oriented approach through strengthened supervisory mechanisms, enhanced legal and digital financial education, and improved coordination among regulatory and law enforcement institutions. Such measures are essential to ensure that fintech innovation develops in a balanced manner, upholds consumer rights, and remains consistent with the principles of the Indonesian rule of law and the foundational values of Pancasila.